Structural features and functional residues important for the activity of an unusual membrane bound O-acyltransferase - Tran, Tam Nguyen Thu (Kansas State University, 2017)
The membrane bound O-acyltransferase (MBOAT) family contains multi-pass membrane proteins that add fatty acids to different compounds. Despite their importance in economic activity and human health, little is known about the localization of the active site and regions important for determining substrate specificity of MBOATs. Euonymus alatus diacylglycerol acetyltransferase (EaDAcT) is the only known MBOAT enzyme that exhibits a high preference for acetyl-CoA, the shortest possible acyl-CoA. EaDAcT catalyzes the transfer of the acetate group from acetyl-CoA to the sn-3 position of diacylglycerol to form 3-acetyl-1,2-diacyl-sn-glycerol. Our goal was to investigate the structural features and the amino acid residues that define substrate specificity of EaDAcT to provide insights into the mechanism by which MBOAT family controls substrate selection. By mapping the membrane topology of EaDAcT we obtained the first experimentally determined topology model for a plant MBOAT. The EaDAcT model contains four transmembrane domains with both the N- and C- termini oriented toward the endoplasmic reticulum lumen. The MBOAT signature region including the putative active site His-257 of the protein is embedded in the third transmembrane domain close to the interface between the membrane and the cytoplasm. In order to identify amino acid residues important for acetyltransferase activity, we isolated and characterized orthologs of EaDAcT from other acetyl-TAG producing plants. Among them, the acetyltransferase from Euonymus fortunei possessed the highest activity in vivo and in vitro. Mutagenesis of conserved residues of DAcTs revealed that Ser-253, His-257 and Asp-258 are essential for enzyme activity of EaDAcT, suggesting their involvement in the enzyme catalysis. Alteration of residues unique to acetyltransferases did not alter the acyl donor specificity of EaDAcT, implying that multiple amino acids are important for substrate recognition. Together, this work identifies the structural features of EaDAcT and offers an initial view of the amino acids important for activity of the enzyme.
Keywords: acetyl-TAG; MBOAT; Membrane topology; Euonymus alatus diacylglycerol acetyltransferase; Wax synthase